Reporting on sustainable operations by third sector organizations: a signaling approach - Simaens, A.; Koster, M. (Public Management Review, 2013)
Awareness of (un)sustainable operations is increasingly researched in the for-profit and government sectors, but little is known about the third sector. Still, these not-for-profit organizations are challenged by progressive accountability requirements and increasingly they seem to be responding to these demands through sustainability reporting. In this paper, we explore sustainability reporting by third sector organizations (TSOs) in the context of signalling theory; a useful theoretical lens to explore organizational reports as a signal to stakeholders. Using a document analysis, we explore twenty-three TSOs to discover what they are signalling, to whom, and whether different organizations send different messages.